PENINGKATAN PEMBERDAYAAN KELOMPOK WANITA TANI DUSUN WONOREJO KOTA BATU MELALUI PELATIHAN PEMBUATAN PRODUK SUSU PROBIOTIK-SARI BUAH SEBAGAI MINUMAN KESEHATAN - Nuzul Wahyuning Diyah; Isnaeni Isnaeni; Asri Darmawati; Suko Hardjono (Universitas Airlangga, 2020)
Wonorejo village in Batu city is known as a vegetable and fruit producing area. Another popular product of Batu mostly is fresh dairy milk and only a small amount of processed products while the cow milk collected in KUD Batu has reached 16-17 tons per day. The problem was that the target community had no experiences in processing cow milk using probiotic microbes. The purpose was transfering of science and technology about the production of probiotic milk combined with fruit juice. This program was specifically directed to increase the empowerment of Kelompok Wanita Tani